Power and Energy Requirements for Carbon Capture and Sequestration - Efstathios E. Michaelides (Thermo)
Carbon capture and sequestration have been recently presented as a viable option to reduce atmospheric carbon dioxide emissions and mitigate global climate change. The concept entails the capture, compression, transportation, and injection of the gas into a medium suitable for storage. This paper examines the thermodynamic and transport properties of carbon dioxide that are pertinent to its sequestration and storage, describes the various methods that have been recommended for its separation from the mixture of the flue gases, and determines the mechanical power and heat rate required for the capture of the gas. The power required for the compression and transportation of the gas by a pipeline is also determined, as well as the effect of the ambient temperature on the transportation power. Calculations for the total power required are performed for two cases, one a cement production unit and the second a coal power plant. The mechanical power needed for the sequestration of CO2 is substantial in both cases, with the cement unit needing less power because of the availability of high-temperature waste heat. In both cases, the equivalent mechanical work needed for the sequestration and storage of this gas is on the order of 1 MJ per kg CO2 sequestered.